RISCOS E POTENCIALIDADES DA ATIVIDADE DE TURISMO RURAL NA MICRORREGIÃO DE PONTA GROSSA - Kloster, Silvana (2013)
The objective of work is to deepen the analysis and understand of tourism in rural areas and the their possibilities analyzing the risks and potentiality activity in family farming in Microregion Ponta Grossa.It is a historical approach regarding rural development in Brazil addressing dualism in agriculture and the inclusion of non-agricultural activities in rural areas, characterized by pluriactivity, an issue that has to be discussed from the 1990. The research was based on exploratory research using information based in the literature review and interviews with agents involved in the development projects with landowners and visitors. Tourism in an active capable of modifying the space turning it in tourism territory where come true power relation among social actors involved with the activity. The tourism area is discontinuous, distinct hierarchical and can be articulated in networks endowed with sense of expressiveness a direction given to those who establishes and/or for anyone who enjoys it. Tourism in rural areas has a differentiated product training conventional tourism or mass tourism; haven seen what is planned as specialized tourism and practiced on a small scale adapted to the characteristic of rural area. Analyzing the risks and opportunities caused by tourism projects in the rural area. Developed together with family farmers we observed that the forms of production are diverse. The different activities can be considered of great potention for local and regional development serving as proposed integrated tourism, ie, combining different activities the demand research showed that lack of play areas, plus the varied actives attract considerable flow of local visitors. As result it was found that the tourism project in rural areas are isolated and discontinuous requiring greated coordination between them, there is not a lot of information about the tourism activity to reach the landowner.Initiatives occur through institutions, but not in a organized for networks of relationships between them. Thus, there is a need knowledge and mediation between owners involved in the projects and technicians responsible for the minimization of insecurity as a risk factor for the investment of tourism active.